Descriptive Analysis of Mathematical Connection Ability in Comparative Materials for Junior High School Students - Supardi Uki Sajiman; Hasbullah Hasbullah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
The purpose of this study was to analyze the mathematical connection ability of the comparative material of junior high school students. This study uses a qualitative approach. Determination of the subject in this study using a purposive sampling technique. The subjects in this study were seventh-grade students of Al-Maghfiroh Junior High School. Data collection techniques in this study used tests and interviews. The results showed that the students' mathematical connection ability was classified as moderate with a percentage of 66.7%. In completing mathematical connections, accuracy is needed to solve mathematical connection problems according to indicators. it is expected to pay more attention to the difficulties experienced by students to improve their mathematical connection skills. Therefore, educators can introduce questions related to everyday life so that students can relate mathematical concepts to everyday life problems